UiTM-UNPAK programme : bridging cultures and fostering sustainable community development with international community service UiTM-UNPAK programme / Muhammad ‘Izzuddin Zamery - Zamery, Muhammad ‘Izzuddin (Faculty of Pharmacy, 2023)
In an era of global interconnectivity, the International Community Service UiTM-UNPAK programme stands as an example of unity in diversity and a commitment to the well-being of communities, with a focus on Desa Pagelaran, Indonesia. This programme is a testament to the power of international collaboration, orchestrated by Universitas Pakuan (UNPAK), Bogor, and supported by the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam Campus, Malaysia. Together, they have created a platform for students from different cultural backgrounds to come together and work towards a common goal.